Fair Performance Appraisal and Its Effects on Organisational Commitment of Lectures in Universiti Utara Malaysia - Pridhivraj, Naidu (2014)
Organizational commitment has been an increasingly researched field of study since the past research shown the important to the organization as a whole. Despite the increase in attention given to the study of workplace commitment, there is still question on the relationship and affects of fairness and its relation to the commitment. This study tries to identify the relationship between the fairness of performance appraisal in the academic community towards the organizational commitment of the lecturers. The current research has been conducted among 316 lecturers in Universiti Utara Malaysia (UUM). A questionnaire survey based research was used to collect data and analyzed using Pearson correlation and linear regression to identify the relationship and test the hypothesis. The findings of this study indicate, that there is a significant and positive relationship between perceived fairness, such as procedural justice, informational justice and interpersonal justice in performance appraisal and organizational commitment. Distributive justice in performance appraisal was found to be not significant in affecting the organizational commitment of lecturers.